Assessment of calprotectin in ascitic fluid as a marker for spontaneous bacterial peritonitis diagnosis in cirrhotic patients - Fayrouz O Selim; Nahawand A El-Deeb; Hesham A Farrag; Azza M Ahmed (The Egyptian Journal of Internal Medicine, 2018)
Background Spontaneous bacterial peritonitis (SBP) is a serious infection of ascitic fluid in cirrhotic patients. High mortality associated with the delay in diagnosis and treatment. There is a need for an accurate and a rapid method for SBP diagnosis. Objectives We aimed to evaluate ascitic fluid calprotectin as a diagnostic marker for SBP. Patients and methods Forty four cirrhotic patients were divided into two groups, non-SBP group: 22 patients with cirrhotic ascites without evidence of SBP and SBP group: 22 patients with cirrhotic ascites and SBP diagnosed by positive ascitic fluid bacterial culture and an increase in polymorphonuclear leukocytes (PMNLs) count in ascites (≥250 cells/mm3). Ascitic fluid calprotectin levels were measured using enzyme-linked immunosorbent assay. Results There was a significant increase of ascitic fluid calprotectin, total leukocytic count, PMNLs, lactate dehydrogenase, and total protein in SBP group when compared to non-SBP group. There were significant positive correlations between white blood cell, ascitic fluid total leukocytic count, PMNLs, total protein, and model for end-stage liver disease score values and ascitic fluid calprotectin among SBP group. Ascitic fluid calprotectin with cutoff value 620 ng/ml, showed a sensitivity of 90.91% and a specificity of 95.45%, in diagnosis of SBP with positive predictive value 95.2% and negative predictive value 91.3%. Conclusion Ascitic fluid calprotectin may be valuable in rapid diagnosis of SBP.